Government Collaboration Of Pentahelix Models In The Management Of Ecotourism D’Bendungan View Telaga Tunjung (Case Study Management of Ecoutourism D’Bendungan View Telaga Tunjung in Timpag Village, Tabanan Bali) - I Made Wimas Candranegara; I Wayan Mirta; I Nyoman Mangku Suryana (Indonesian Association for Public Administration (IAPA), 2019)
The development of nature and cultural based tourism by developing the potential of tourism villages by raising the natural and cultural potential is believed to strengthen local social and cultural resilience. Telaga Tunjung Dam is one of the largest dams in Bali, which is precisely in Timpag Village, Kerambitan District, Tabanan Regency. Seeing the potential of the natural landscape possessed by Telaga Tunjung Dam, the Timpag Village community group incorporated in Paiketan Krama Rantauan Timpag (Pakerti) formed a D'Bendungan View natural recreation vehicle that offers three features, namely the selfie vehicle, culinary stalls and area meeting. In the management and development of tourism, a coordination and collaboration between the government, tourism businesses, communities, academics, and media is needed, called Pentahelix collaboration in developing tourism potential.